2017
DOI: 10.1111/jcms.12647
|View full text |Cite
|
Sign up to set email alerts
|

Legitimizing Europe in Contested Settings: Europe as a Normative Power in Turkey?

Abstract: This article aims to explore whether – and if so, how – the EU is perceived as a normative power (NPE) in Turkey in the context of deteriorating Turkey–EU relations. By adopting the Habermasian understanding that legitimacy is a prerequisite for NPE and through employing a focus group methodology novel to NPE research, the article finds that a certain segment of the Turkish public views the EU as a normative power, suggesting that claims for the existence of NPE need to be qualified both by the level of analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Aydın-Düzgit's more recent work moved the focus from elite constructions of national identity to those of the public by exploring via focus group methodology whether the discursive shifts in the AKP's debate on Europe led to changes in public constructs of national identity. She found that the AKP's representation of Europe as politically and/or economically inferior to Turkey and Turkey's representation as a superior nation to Europe, thanks to its unique Ottoman history, had penetrated public discourse; however, Europe was also increasingly associated with normative values such as democracy and human rights in Turkey, particularly among those who identified themselves with the left-wing opposition parties (Aydın-Düzgit, 2018a, 2018b.…”
Section: -2020: Freezing Of Accession Negotiations and The Period Of Conflictual Cooperationmentioning
confidence: 99%
“…Aydın-Düzgit's more recent work moved the focus from elite constructions of national identity to those of the public by exploring via focus group methodology whether the discursive shifts in the AKP's debate on Europe led to changes in public constructs of national identity. She found that the AKP's representation of Europe as politically and/or economically inferior to Turkey and Turkey's representation as a superior nation to Europe, thanks to its unique Ottoman history, had penetrated public discourse; however, Europe was also increasingly associated with normative values such as democracy and human rights in Turkey, particularly among those who identified themselves with the left-wing opposition parties (Aydın-Düzgit, 2018a, 2018b.…”
Section: -2020: Freezing Of Accession Negotiations and The Period Of Conflictual Cooperationmentioning
confidence: 99%
“…Initially, most research on external perceptions continued to revert to eurocentric question: ‘What do you think of the EU and of EU norms ?’ as opposed to the more engaging ‘What do you think of norms?’ or ‘Which norms do you consider to be important?’ (Fisher Onar and Nicolaïdis, 2013, p. 289), and therefore rarely went beyond observations of (mis)perceptions and contestation. Gradually, more analyses have emerged that do engage with third country's perspectives of norms, including those in Turkey (Aydin‐Düzgit, 2018), China (Kavalski, 2017), Russia (Romanova, 2016) and Africa (Staeger, 2016). These point to different dispositions to norm orientations that may explain (mis)perceptions and contestation.…”
Section: Provincializing: Unpacking Eu Normative Actornessmentioning
confidence: 99%
“…The continua are designed to support scholars in discovering, interpreting and contextualizing the normative inclinations in a society, country or region, keeping in mind that major differences may also exist within polities (Aydin‐Düzgit, 2018) and can vary per issue and over time. Indeed, identifying norm orientations is particularly complex in countries and regions where purely national identities are relatively recent or where policy stances are influenced by authoritarian forms of governance or other strong subnational and supra‐national normative frameworks.…”
Section: Continua Of Norm Orientationsmentioning
confidence: 99%
“…In addition to the power differential between the two countries, part of the reason also has to do with the fact that Turkey is formally a candidate country conducting accession negotiations with the EU since 2005. During the time that Turkey embarked on the process of Europeanization in the 2000s, despite some domestic contestation, the normative power of the EU in transforming Turkish governance was largely acknowledged by the government and the main opposition (Aydın-Düzgit, 2018) and rather than contesting the EU in its foreign *We are grateful to Henrik Larsen, Frank Schimmelfennig and the three anonymous reviewers for their comments on the earlier drafts of this paper. We would also like to thank Mehmet Yaşar Altundağ and Abdullah Esin for research assistance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the power differential between the two countries, part of the reason also has to do with the fact that Turkey is formally a candidate country conducting accession negotiations with the EU since 2005. During the time that Turkey embarked on the process of Europeanization in the 2000s, despite some domestic contestation, the normative power of the EU in transforming Turkish governance was largely acknowledged by the government and the main opposition (Aydın‐Düzgit, 2018) and rather than contesting the EU in its foreign policy, Turkey tried to use its albeit weak prospect of accession as an asset in furthering its presence in its surrounding regions (Kaliber and Kaliber, 2019, p. 7). However, as the membership perspective turned increasingly sour in the 2010s and the EU's normative projection on Turkey began to be heavily contested inside with the country's turn towards competitive authoritarianism (Esen and Gumuscu, 2016) and anti‐Westernism (Kaliber and Kaliber, 2019), Turkey's distance with the EU in foreign policy orientations also grew (Kutlay and Öniş, 2021).…”
Section: Introductionmentioning
confidence: 99%